Morphological Character and Trichomes of Daun Gatal (Laportea decumana (Roxb.) Wedd) in Different Natural Shades in Manokwari, West Papua - Desiana Sua'; Fajar Ria Dwi Natalia Sianipar; Paskalina Theresia Lefaan; Slamet Arif Susanto; Johanis Paulus Kilmaskossu (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Daun gatal (Laportea decumana (Roxb.) Wedd.) is a medicinal plant traditionally used by local Papuan communities as a physical therapy to relieve fatigue, muscle pain, and body aches. However, the ecological aspects of its cultivation remain poorly understood. This study aimed to compare the leaf morphological variables of daun gatal cultivated under shaded and unshaded conditions. Field observations were conducted alongside leaf morphometric analysis and examination of leaf trichome characteristics to strengthen the analytical results. The findings indicated that air temperature, air humidity, and sunlight intensity were positively correlated ( 0.80) with plant height, leaf area, trichome length, and trichome density in plants grown under shaded conditions. Meanwhile, plant height and stem diameter did not differ significantly (P>0.05) between shaded and unshaded treatments. In contrast, leaf length, leaf width, and leaf area showed significant differences (P<0.05) between the two treatments. Trichomes of plants grown in shaded habitats were significantly longer than those in unshaded habitats (P<0.05). Trichome density exhibited a similar pattern, being higher in shaded areas than in unshaded areas, although the difference was not statistically significant (P>0.05). Overall, this study demonstrates that the daun gatal exhibits morphological adaptations to variations in light intensity within its habitat, providing an important scientific basis for the effective management and optimal cultivation of Laportea decumana in Manokwari Regency.